PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STDENT TEAMT ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 80 BUMBUNG - Tionom Silaban; Rini Dian Anggraini; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve mathematics learning outcomes in fifth grade students of SD 80 Bumbung by implementing cooperative learning model Students Teams Achievement Division (STAD). The subjects in this study were fifth grade students consisting of 12 male and 13 female with the heterogeneous academic ability. This research is a class act consisting of two cycles. Each cycle consisted of three meetings and one-time Daily Deuteronomy (UH) which was held at the end of each cycle. This study also consists of four stages, namely planning, implementation, observation and reflection. The result of observations indicate the teachers and students activities have performing well after the action. After UH held at the end of the cycle, the number of students who achieve a score is increase of KKM compare to the basic score. With this increasing, the results of research carried out showed that the implementation of STAD cooperative learning model to improve mathematics learning outcomes in fifth grade students of SD 80 Bumbung in the odd semester of the academic year 2013/2014.Keywords: Learning Processes, Results Learning Mathematics, Cooperative Learning, STAD, Classroom Action Research